2014
DOI: 10.1891/0889-8391.28.3.156
|View full text |Cite
|
Sign up to set email alerts
|

The Vietnam Multicomponent Collaborative Care for Depression Program: Development of Depression Care for Low- and Middle-Income Nations

Abstract: In this article, we discuss the Vietnam Multicomponent Collaborative Care for Depression Program, which was designed to provide evidence-based depression care services in low-resource, non-Western settings such as Vietnam. The article provides the program development background; the social, economic, and political context in which the program was developed; and the structure and content of the program and their underlying rationale in the context of rural Vietnam. Although the program was found to be acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…In our opinion, the study results may also be generalisable to the whole population of Vietnam, due to the uniform organisation of the Vietnamese national healthcare system. Integrating the intervention in the primary healthcare setting would result in an improvement of access to mental healthcare service, reduce stigma due to the provision of treatment through non-mental health specialists [5] and allow the detection of depression at an earlier stage of severity, thus potentially preventing suicide. Also, timely treatment may thus be ensured through the intervention for people in greatest need [16].…”
Section: Relevance Of Findings For Practice and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion, the study results may also be generalisable to the whole population of Vietnam, due to the uniform organisation of the Vietnamese national healthcare system. Integrating the intervention in the primary healthcare setting would result in an improvement of access to mental healthcare service, reduce stigma due to the provision of treatment through non-mental health specialists [5] and allow the detection of depression at an earlier stage of severity, thus potentially preventing suicide. Also, timely treatment may thus be ensured through the intervention for people in greatest need [16].…”
Section: Relevance Of Findings For Practice and Further Researchmentioning
confidence: 99%
“…One approach to realise that is by task-shifting [5,14], which relies on training non-mental health workers in depression screening and treatment while supervised by mental health specialists. Studies in other resource-scarce settings have demonstrated the effectiveness of simple treatments provided by non-mental health workers [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, as depression treatment was not controlled for, it is possible that some received depression treatment elsewhere during the three-month study period. However, the chance was minimal because depression care was very limited in Vietnam [34]. Mental health services, even in big cities such as Hanoi and Ho Chi Minh city, do not focus on depression but mainly on schizophrenia, bipolar disorder, and epilepsy [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the chance was minimal because depression care was very limited in Vietnam [34]. Mental health services, even in big cities such as Hanoi and Ho Chi Minh city, do not focus on depression but mainly on schizophrenia, bipolar disorder, and epilepsy [34]. Finally, since this is an observational study without a comparison group, many factors which could affect depression could not be fully controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation